Thermodynamic performance assessment of an integrated ORC-VCRC system coupled with a PEM electrolyzer for hydrogen production using R1233zd(E)/R152a-AlO - Aktemur, Cenker; Kavasogullari, Baris; Gurgenc, Ezgi (Springer Heidelberg, 2026)
The present investigation presents a new configuration of an integrated system based on Organic Rankine Cycle-Vapor Compression Refrigeration Cycle-Proton Exchange Membrane (ORC-VCRC-PEM) electrolysis using nanoparticles-doped working fluids with low Global Warming Potential (GWP). Although previous studies have investigated ORC-VCRC systems and ORC-based hydrogen production, the specific combination of these cycles with a PEM electrolyzer and nanorefrigerants has not yet been explored, which would characterize the originality of the present work. The proposed system utilizes R1233zd (E) in the ORC, R152a in the VCRC, along with alumina (Al2O3) nanoparticles to improve the heat transfer efficiency. The main contribution of this paper to the body of knowledge is the development of a new concept for the integration of ORC-VCRC-PEM with nanoparticles, whose thermodynamic characteristics are evaluated under different operational conditions. The results demonstrate that the proposed system consistently outperforms the conventional system across all investigated operating conditions. Compared to the conventional system, the overall coefficient of performance (COP) improves up to 21.99%, while the overall exergy efficiency increases by up to 20.48%. Total exergy destruction is reduced up to 18.03%, indicating enhanced internal temperature matching and reduced irreversibilities. Hydrogen and oxygen production rates range up to 34.32% depending on evaporator, condenser, and connected IHX temperatures. Overall, proposed system provides significant enhancements in terms of thermodynamics and electrochemistry, which can lead to an attractive solution for modern multi-generation systems that provide cooling and produce sustainable hydrogen.
Keywords: Organic Rankine Cycle; Vapor Compression Refrigeration System; Proton Exchange Membrane Electrolysis